Ultrasound color-flow imaging on a programmable system. - Shamdasani, V. (IEEE Transactions on information technology in biomedicine)
Color-flow imaging is a well-established ultrasound mode and very valuable for visualizing in real time the distribution of blood flow in a specific region of interest. However, it is computationally quite expensive. To meet the large computational need in color-flow imaging, most ultrasound systems have been designed using fixed-function hardware. In this paper, we present a system where all the color-flow processing is supported on a programmable platform. About 95% of the processing modules were programmed in C language. On a single processor, we were able to achieve 7.9 frames/s, when the input data consist of 192 × 512 × 8 (ensemble size) samples for color flow and 384 × 512 for B mode and the output image size is 600 × 420. Additional processors can be added to handle more input data and/or support higher frame rates. Our results demonstrate that a programmable ultrasound system can provide the same functionality for clinical use as conventional ultrasound systems. However, it is more flexible and efficient due to its programmability.